An Empirical Verification of the Fertility Preferences of Urban Women in a Depressed Economy: Evidence from Calabar, Nigeria - Bisong, Francis E.; Animashaun, Adebayo I.; Essien, Elizabeth Andrew (Mediterranean Journal of Social Sciences, 2011)
This work sets out to investigate the fertility preferences of urban women in a depressed economy, using Calabar, Nigeria as acase study. Using a utilizing questionnaire, empirical data were collected from a spatially stratified random sample of urban women andanalyzed, using simple correlation techniques. Family income was made to predict fertility levels, number of children alive, the idealnumber of children per family, the number of children desired per family, and so on. Although the analyses produced both negative andpositive relationships, some are significant while others are not. Therefore, this work has suggested areas in which future researches need beintensified.